2022
DOI: 10.1097/cco.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of sarcomas with modified T cells

Abstract: Purpose of reviewTo summarize the development of modified T-cell therapies in sarcomas and discuss relevant published and ongoing clinical trials to date. Recent findingsNumerous clinical trials are underway evaluating tumor-specific chimeric antigen receptor T cells and high affinity T-cell receptor (TCR)-transduced T cells in sarcomas. Notably, translocation-dependent synovial sarcoma and myxoid/round cell liposarcoma are the subject of several phase II trials evaluating TCRs targeting cancer testis antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Studies have found that HLA-A*02 is more common in Caucasian populations compared to African-American and Asian populations ( 63 ). Other barriers for ACT include the multi-week time needed for the production of genetically engineered T-cells, the pre-treatment lymphodepletion regimen which often requires hospitalization, and the high cost of therapy ( 64 , 65 ). While many of these issues may be overcome through improvement in manufacturing techniques and health systems changes, some may be incontrovertible.…”
Section: Syn Antigen Expression and Adopted Cell Transfermentioning
confidence: 99%
“…Studies have found that HLA-A*02 is more common in Caucasian populations compared to African-American and Asian populations ( 63 ). Other barriers for ACT include the multi-week time needed for the production of genetically engineered T-cells, the pre-treatment lymphodepletion regimen which often requires hospitalization, and the high cost of therapy ( 64 , 65 ). While many of these issues may be overcome through improvement in manufacturing techniques and health systems changes, some may be incontrovertible.…”
Section: Syn Antigen Expression and Adopted Cell Transfermentioning
confidence: 99%
“…GD-2-specific CAR-T cells, as well as CAR-T cells specific to other sarcoma markers, CD133, HER2, Muc1 and CD117 are being tested in clinical trials (NCT03356782, NCT03356782, NCT04433221). Therapeutic approaches in sarcoma based on modified T cells have recently been reviewed [178]. However, the HLA restriction of T-cell-based therapies to prevent GvHD, limits the streamlining of the manufacturing processes and limit the therapy mainly to autologous sources.…”
Section: Nk Cell Engineeringmentioning
confidence: 99%